Using the behaviour change technique taxonomy v1 (BCTTv1) to identify the active ingredients of pharmacist interventions to improve non-hospitalised patient health outcomes. Issue 9 (15th September 2020) - Scott, Claire; de Barra, Mícheál; Johnston, Marie; de Bruin, Marijn; Scott, Neil; Matheson, Catriona; Bond, Christine; Watson, Margaret C
Abstract : Objectives: The aim of this study was to identify which behaviour change techniques (BCTs) were present in intervention and control groups of randomised controlled trials (RCTs) included in a Cochrane systematic review. Setting: The RCTs included were conducted in community, primary and/or ambulatory-care settings. Participants: The data set was derived from 86 RCTs from an interim update of the Cochrane review of the effectiveness of pharmacist services on non-hospitalised patient outcomes. Primary and secondary outcome measures: The primary outcome was the identification of BCTs scheduled for delivery in intervention and control groups of the RCTs. The secondary outcome measure was to identify which BCTs are not being utilised in intervention and control groups of the RCTs. Results: The intervention and control groups included 31 and 12 BCTs, respectively. The number of identifiable BCTs/study ranged from 0 to 12 in the intervention groups (mean 3.01 (SD 2.4)) and 0 to 6 in the control groups (mean 0.38 (SD 0.84)). The most commonly identified BCTs in the intervention groups were: instruction on how to perform the behaviour (55%, n=47) (also the most common BCT in control groups); problem solving (29%, n=25); information about health consequences (24%, n=21); social support (practical) (24%, n=21); and social support (unspecified) (23%, n=20) (the second most common BCT in control groups). Thirteen trials had no identifiable BCTs in either group. Conclusion: The pharmacist interventions presented in this study did not use the full range of available BCTs. Furthermore, the reporting of BCTs was incomplete for both intervention and control groups, thereby limiting the utility and reproducibility of the interventions. Future interventions should be designed and reported using relevant taxonomies and checklists for example, BCT taxonomy and TIDieR (the template for intervention description and replication).